PENERAPAN JIGSAW LEARNING MELALUI WHATSAPP UNTUK MEMAHAMI MATERI QURAN HADITS SURAH AL-HUMAZAH - Husniyatus Salamah Zainiyati; Siti Munawaroh; Rudy Al Hana; Lailatul Badriyah (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2021)
Abstract: The learning model of the teacher must be in accordance with the conditions and needs of the students, in order to create active, creative, effective and enjoyable learning. So that the subjects of Quran Hadi-th will be easier to learn and understand the content of its contents and help students in practicing it daily. To achieve these expectations, in learning Quran Hadith using jigsaw learning model through WhatsApp appli-cation. The aims of this research is to describe the application of jigsaw learning through WhatsApp Group, to understand Surah Al-Humazah in the lear-ning of Quran Hadith in grade 5 MI Thoriqul Ulum Lamongan. This type of research is quantitative and qualitative collaboration with data collection method using observation and interview. Data analysis tech-niques use descriptive quantitative and qualitative. The results were obtained that with jigsaw learning through WhatsApp Group can improve the skills, understanding and activeness of learners than before. With an average class, student achievement reached 85.63. Reading or memorizing Surah Al-Humazah using reading guide and reading aloud through voice note feature. Card sort feature to understand the meaning of per-verse and Everyone is a Teacher Here is applied to understand the content of Surah Al-Humazah.Keywords: Jigsaw Learning, Whatsapp, Quran Hadits